Developing affordable housing : a practical guide for nonprofit organizations - Hecht, Bennett L., 1959- (New York : John Wiley and Sons, 1999)
Getting started. Projecting costs, income, and expenses. Raising capital. Enhancing feasibility and packaging the project. Purchasing and developing the property.
Keywords: United States; Housing development; Housing development -- United States -- Handbooks, manuals, etc; Housing rehabilitation -- United States -- Handbooks, manuals, etc; Housing management -- United States -- Handbooks, manuals, etc; Nonprofit organizations -- United States -- Handbooks, manuals, et